2019
DOI: 10.1186/s12985-019-1203-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the virucidal effects of rosmarinic acid against enterovirus 71 infection via in vitro and in vivo study

Abstract: Background Although enterovirus 71 (EV71) is an important public health threat, especially in the Asia-Pacific region, there are still no effective drugs or vaccines to treat and prevent EV71 infection. Therefore, it is critical to develop prophylactic and therapeutic agents against EV71. Rosmarinic acid (RA), a phytochemical, has been discovered to possess a broad spectrum of biological activities. Methods The virucidal effects of RA on EV71 were determined by MTT, wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Rosmarinic acid (RA), an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid ( Figure 1A) found in Danshen, exhibits antioxidant, anti-inflammatory, anti-bacterial, and antiviral properties [23][24][25][26]. RA has also been previously shown to possess anti-EV-A71 activity, as it inhibits virus entry [22,27]. However, the underlying molecular mechanism remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acid (RA), an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid ( Figure 1A) found in Danshen, exhibits antioxidant, anti-inflammatory, anti-bacterial, and antiviral properties [23][24][25][26]. RA has also been previously shown to possess anti-EV-A71 activity, as it inhibits virus entry [22,27]. However, the underlying molecular mechanism remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [6] found that rosmarinic acid could protect cells from the pathological changes induced by enterovirus 71 (EV71), and the inhibitory activity of rosmarinic acid was the strongest at the early stage of EV71 infection, which could be used as an antiviral drug for EV71 infection in the early stage of treatment. In addition, rosemary extracts can also inhibit the replication of influenza virus and has a therapeutic effect on virus-induced pneumonia injury.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…In silico study predicts that rosmarinic acid can replace the natural receptacle factor in the VP1 capsid-binding hydrophobic vessel. 29 Rosmarinic acid has an excellent opportunity as an antiviral candidate to inhibit replication and reduce the adverse effects caused by EV71 infection because rosmarinic acid is effective in reducing EV71 viral infection in the early stages. Rosmarinic acid acts in the early stages of viral infection and can target viral particles directly to affect the interaction between virus-P-selectin glycoprotein ligand-1 (PSGL1) and virus-heparan sulfate.…”
Section: Anti Enterovirusmentioning
confidence: 99%
“…89 Tanshinone ⅡA inhibits Tat-induced Transactivation of LTR HIV-1 depending on the AMPK-Nampt pathway so that it can be developed into a new anti-HIV agent, 90 oleanolic acid inhibits HIV-1 replication by inhibiting HIV-1 protease activity in vitro, 91,92 and maslinic acid has potent inhibitory activity against HIV-1 proteases. 93 Ladanein Anti-HCV hepatitis C virus (HCV) activity 83 Sinensetin -Treatment of influenza disease with excessive inflammation 31 -Inhibitors of SARS-CoV-2 Guanine-N7 Methyltransferase (in silico study) 77 Cirsimaritin -Inhibitors of COVID-19 main protease (in silico study) 78 -Anti-influenza virus 95 Phenolic Acid 96,43,97,98 Rhamnazin Anti-HCV hepatitis C virus (HCV) activity 99 Rosmarinic acid -Anti enterovirus 71 (EV71) 29,30 -Potential inhibitor of COVID-19 (in silico study) 32,33,73 -Reduces the mortality of mice infected with the Japanese encephalitis virus (JEV) 34 -Inhibit hepatitis B virus replication 36 Caffeic acid -Anti-herpes simplex virus type 1 54 -Inhibition influenza A virus multiplication in vitro 67…”
Section: Anti-human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 1 more Smart Citation